The utilization of biodiesel from waste cooking oil for Unand campus buses in Padang, Indonesia - Yandri, Valdi Rizki (Jurnal Spektra, 2011)
Waste Cooking Oil (WCO) as the waste from household, restaurant and food entrepreneur will be processed to biodiesel. It will be used only for campus buses of University of Andalas (Unand) in Padang, West Sumatera, Indonesia. Noticeably, the campus buses fuel not only consist of biodiesel but also petrodiesel too, i.e. 5% biodiesel and 95% petrodiesel. Unand has four types of campus bus. i.e. 27 white microbus, 7 white bus, 4 green bus and 1 exclusive bus with the total weekly petrodiesel consumption is 9,625 L. It means we need 414 L WCO to produce biodiesel. Furthermore, this utilization can support Indonesian government in energy conservation program, i.e. saving the petrodiesel consumption and increasing biodiesel utilization as renewable energy.Â Keywords: Petro diesel, biodiesel, waste cooking oil, energy conservation.